A Multifaceted Analysis of Land Acquisition Act 1894: Unpacking Legal, Religious and Social Implications - Naveed Hussain; Yasir Arfat (Dialogue Social Science Review (DSSR), 2025)
Purpose of this study is to focus on the Compulsory land acquisition law that disowns the individuals from their properties and assets which are constitutionally protected. It is done on the pretext of public good. Undoubtedly Islamic Law also permits the public rights and individual rights are there to stand subject to the public rights. But this study has focused on the aspects that how the acquisition practices in Pakistan are Shariah compliant as in such transactions it is not only the purpose that statutory requirements are met and transparency and fairness is propagated but that transparency is supposed to be seen in the actual transactions. If that is not the spirit, then worldly affairs can be settled but the lawgiver (Almighty Allah) cannot be deceived and he is well aware of all the affairs. The study also focused on the problems which are not being addressed because of obsolete legislation and recommendations have been advanced that the issue can be overcome. It is also pertinent to mention that Courts have adopted a dual attitude that while making the decisions courts are under constitutional obligation that there should not be anything which is supported, promoted, interpreted or implemented which is against the injunctions of Quran and Sunnah. At the same time Courts have been found to implement the intention of legislature which may or may not be adhering to the Golden principles laid down by Quran and Sunnah. Restrictive approach has been found in the legislation that puts the public at Large in a state of chaos and public loses its trust in the state and its institutions. The study concludes with practical solutions to deal with problem.